Piwulang melalui martabat tujuh dalam teks Serat Asmaralaya - Mulyani, Hesti (Kejawen, 2025)
Piwulang, or Javanese moral teaching, needs greatly to be given to the young generation nowdays. As rthe next torch of the nation, they need to be armed with strong moral foundations in order not to be easily swayed indecisively in to different directions and in order to be able to overcome the various obstacles in life in positives ways. It is therefore considered necessary to conduct research on such moral teaching to offer alternative solutions for the needs of those who will continue the life of the nation and to revive the old Javanese moral teaching contained in the next of Serat Asmaralaya. Elaborated in Serat Asmaralaya are the basic idea of the teaching about manunggaling Kawula-Gusti (martabat tujuh) are (1) eling (remembering) man's nature as kawula (subject), (2) knowing the essence of God, (3) endeavoring to be insan kamil (the ideal man), and (4) knowing ways of facing death.